PENERAPAN APLIKASI MYOB ACCOUNTING VERSI 18 DALAM PENYUSUNAN LAPORAN KEUANGAN PADA CV. TANI JAYA KABUPATEN PURWOREJO - Dean Mutiara; Supriono Supriono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2022)
Economic development in Indonesia is now very fast and there are increasing numbers of increasingly competitive business competitors. The company’s ability to generate profits it the key to the company’s success. Because, this will affect the sustainability of the company to move forward and influence cooperation between one company and another company. For this reason, it is necessary to have a financial report to help smooth the company in making decisions and predict the condition of the company in the future. Preparation of financial statements at CV. Tani jaya is done by inputing the company’s initial data, inputing transaction data, the printing financial reports as January 31 by using MYOB Accounting v18 application. The purpose of this study is to know how big the benefits of preparation of financial statements at CV. Tani Jaya by using MYOB Accounting v18 application.. The results of the research in this Final Project report concluded that the financial statements made by CV. Tani Jaya by using MYOB Accounting v18 application consist of the income statement and statement of financial position as of January 31, 2019 which are prepared in accordance with the SAK EMKM. The financial statements are made to find out information about the income statemenet and statement of financial position so that it can be used as a means of decision making in the future. While the application is used so that the process of making financial statements is faster and more accurate .